ANALISIS BIAYA DAN WAKTU PERCEPATAN PEKERJAAN PROYEK KONSTRUKSI DENGAN MENGGUNAKAN PELAT BONDEK - Risky Andika Purnama; Paksitya Purnama Putra; Hernu Suyoso (Fakultas Teknik, Universitas Wiraraja, 2020)
Bondek slab is a composite slab consisting of galvanized steel, wiremesh and concrete. Compared to conventional slab, bondek slab themselve are still not applied to often in Indonesia because it requires special calculations to use them. The purpose of the study are to calculate the budget and period of slab work by using the bondek slab method and determine the budget and period efficiency of using the conventional slab and bondek slab. To find this out, analysis is carried out starting from structur analysis, volume analysis, budget analysis and period analysis. The analysis shows that the slab can reduce the cost of slab implementation is 35.45% or Rp. 1,223,932,278.33 and accelerate the time for floor slab work is 36.21% or 63 days, which originally used conventional floor slab cost is Rp. 3,452,222,761.32 and the duration of work is 174 days. While if use a bondek slab only costs is Rp. 2,228,290,482.99 and the duration of work is 111 days.